CCAFS Business Plan 2012 - CGIAR Research Program on Climate Change, Agriculture and Food Security (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2012)
2012 will be the second year of operation of the CGIAR research program on Climate Change, Agriculture and Food Security (CCAFS). The 2012 business plan lays out the key activities in 2012, situated within the larger strategic framework of CCAFS. At the time of writing, many of the overarching principles for the operation of CGIAR Research Programs (CRPs) are still being produced by the Consortium Office (e.g. monitoring and evaluation strategy), so some of the proposed activities in 2012 may need to be modified as the year unfolds.